2018
DOI: 10.9734/jpri/2018/39412
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Investigations of Ethanolic Leaves Extract of Dissothis thollonii (Melastomataceae)

Abstract: Dissotis thollonii is widely used in Cameroon for the treatment of typhoid fever, gastrointestinal disorders, inflammation, kidney diseases, pregnancy control and sinusitis. However there is lack of experimental data on its possible toxicity. The aim was to investigate acute and subchronic toxicity of the ethanol leaf extract of Dissotis thollonii in healthy Wistar rats. In acute toxicity tests, a single administration of the ethanolic leaf extract (5000 mg/kg) of Dissotis thollonii was given orally to 4 femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…thollonii , which is a pantropical plant from the Melastomataceae family. It is traditionally used to treat sinusitis, typhoid fever, inflammatory diseases, and gastrointestinal disorders [ 22 ]. The plant has proven numerous activities such as antidiarrheic, antibacterial, antimicrobial, antioxidant, and antiulcerogenic activities [ 23 – 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…thollonii , which is a pantropical plant from the Melastomataceae family. It is traditionally used to treat sinusitis, typhoid fever, inflammatory diseases, and gastrointestinal disorders [ 22 ]. The plant has proven numerous activities such as antidiarrheic, antibacterial, antimicrobial, antioxidant, and antiulcerogenic activities [ 23 – 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comprising about 163 genera, the family of Melastomataceae which are mainly pantropical plants include more than 4,300 species so many of them are known for their effectiveness in traditional medicine as antihepatitic, antihypertensive, anti-inflammatory, antihyperglycaemic, antioxidant, hemostatic, and antidiarrheal [19–24]. Dissotis thollonii ( D. thollonii ) is one of many species of the family of Melastomataceae used in traditional medicine in Cameroon to treat typhoid fever, gastrointestinal disorders, inflammatory diseases, and sinusitis [25–27]. The leaves are recommended for the treatment of ulcers and gastrointestinal disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the work of TadjouaTchoumbou et al [24] showed that this plant significantly inhibited leukocyte migration in peritoneal fluid, intracellular ROS production, proliferation of Hela cell lines, and TNF- α production. Tala et al [27] showed that aqueous and ethanolic extracts were devoid of toxicity after 28 days of daily treatment. Similarly, Nono et al [30] showed the antimicrobial and antioxidant properties of this plant.…”
Section: Introductionmentioning
confidence: 99%